2019
DOI: 10.1007/s12254-019-0493-6
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to immune checkpoint inhibitors. Next steps and combinational approaches

Abstract: Immuno-oncology and in particular checkpoint inhibitor (CPI) treatment has become a novel promising cancer therapy strategy in recent years. However, still a minority of patients respond to checkpoint blockade. Primary and secondary resistance to CPI is a challenge in the daily clinical routine. Combination strategies have been tested in various clinical trials in order to address this issue. Data available from these trials indicate improved activity depending on the tumor type. This review article focuses on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Here, the role of Tregs, myeloid-derived suppressor cells (MDSCs) and type II macrophages is highlighted, as well as that of regulatory molecules released in the TME, such as IFN-γ, IDO, CEACAM1, TIM-3, TGF-β or adenosine [ 80 , 86 ]. Other host factors that also influence treatment resistance include endocrine, metabolic, environmental (dysbiosis, antibiotic or steroid consumption) and personal factors (age, chronic disease or genetic susceptibility) [ 87 ]. Additionally, different resistance mechanisms (primary/secondary) and antitumor immunity converge depending on the tumor phenotype.…”
Section: Resistance To Immune Checkpoints In Lung Cancer Immunothementioning
confidence: 99%
See 2 more Smart Citations
“…Here, the role of Tregs, myeloid-derived suppressor cells (MDSCs) and type II macrophages is highlighted, as well as that of regulatory molecules released in the TME, such as IFN-γ, IDO, CEACAM1, TIM-3, TGF-β or adenosine [ 80 , 86 ]. Other host factors that also influence treatment resistance include endocrine, metabolic, environmental (dysbiosis, antibiotic or steroid consumption) and personal factors (age, chronic disease or genetic susceptibility) [ 87 ]. Additionally, different resistance mechanisms (primary/secondary) and antitumor immunity converge depending on the tumor phenotype.…”
Section: Resistance To Immune Checkpoints In Lung Cancer Immunothementioning
confidence: 99%
“…Immunoexcluded tumors are able to evade stromal factors as a result of mechanical barriers, vascular factors or an immune-suppressive chemokine state. In the case of immunoinflammed tumors, all the mechanisms mentioned above come together [ 87 ]. In addition, Syn et al [ 88 ] observed a parallelism between the primary and secondary resistance mechanisms.…”
Section: Resistance To Immune Checkpoints In Lung Cancer Immunothementioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to immunotherapy can be classified as primary (or innate) and secondary or acquired [12][13][14][15]. Some authors also refer to an intermediate phenotype that is adaptive resistance [16].…”
Section: Introductionmentioning
confidence: 99%
“…Wieser et al [3] discuss novel approaches as PARP (poly ADP ribose polymerase) inhibition and forecast that therapy may require different approaches depending on the molecularly defined subgroups of OC ("differentiated", "immunoreactive", "mesenchymal" and "proliferative"). Furthermore, Fuereder [4] gives an overview on immunotherapy resistance and focuses on the molecular background of resistance to checkpoint inhibition (CPI) and outlines current clinical data of CPI combination studies. Future potential strategies to overcome CPI resistance might also depend on the immune phenotype.…”
mentioning
confidence: 99%